Glucose Metabolism Effects of Vitamin D in Prediabetes: The VitDmet Randomized Placebo-Controlled Supplementation Study - Tomi-Pekka Tuomainen; Jyrki K. Virtanen; Sari Voutilainen; Tarja Nurmi; Jaakko Mursu; Vanessa D. F. de Mello; Ursula Schwab; Martti Hakumäki; Kari Pulkki; Matti Uusitupa (Journal of Diabetes Research)
Epidemiological evidence suggests a role for vitamin D in type 2 diabetes prevention. We investigated the effects of vitamin D3 supplementation on glucose metabolism and inflammation in subjects with prediabetes. A 5-month randomized, double-blind, placebo-controlled intervention with three arms (placebo, 40 μg/d, or 80 μg/d vitamin D3) was carried out among sixty-eight overweight (BMI 25–35) and aging (≥60 years) subjects from Finland, with serum 25-hydroxyvitamin D3 [25(OH)D3] < 75 nmol/L and either impaired fasting glucose or impaired glucose tolerance. Analyses included 66 subjects who completed the trial. Glucose metabolism was evaluated by fasting and 2-hour oral glucose tolerance test-derived indices and glycated hemoglobin. Inflammation was evaluated by high-sensitive C-reactive protein and five cytokines. Although a dose-dependent increase in serum 25(OH)D3 over the supplementation period was observed (P trend < 0.001), there were no other statistically significant differences in changes in the 13 glucose homeostasis indicators between the study groups other than increase in the 120 min glucose concentration (P trend = 0.021) and a decreasing trend both in 30 min plasma insulin (P trend = 0.030) and glycated hemoglobin (P trend = 0.024) concentrations. A borderline statistically significant decreasing trend in interleukin-1 receptor antagonist concentration was observed (P = 0.070). Vitamin D3 supplementation does not improve glucose metabolism in ageing subjects with prediabetes but may have modest anti-inflammatory effects.